2013
DOI: 10.1063/1.4811945
|View full text |Cite
|
Sign up to set email alerts
|

A method for structural analysis of disordered particle systems

Abstract: Abstract. We present a brief overview of a method which can identify different 3D local structures in ordered and disordered systems. Its effectiveness is demonstrated in the analysis of the structures of sphere packings, the structural evolution of a rapid cooling process of silver liquid, and the inner structure of a metal nanocluster. Quantifying local structures by means of a topological criterion, this method is parameter-free and scale-independent, and can generally be used for structural analysis of amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…In the present work, a molecular dynamics (MD) simulation is used to investigate the evolution of microstructures of Si 50 Ge 50 nanoparticles during solidification. The internal microstructure of nanoparticles is examined by the pair distribution function (PDF), the coordination number (CN), and the largest standard cluster (LaSC). It is found that Si 50 Ge 50 nanodroplets with some metallicity are cooled into a crystal without element segregation through four stages, and the saturation of the covalent bond is satisfied before the directionality in the crystallization process. Interestingly, there exists a CNC state, where the average size of the crystalline structure is independent of temperature but depends on the cooling rate; and the heritability of basic crystalline atoms is not over 50% until the end of the CNC state.…”
Section: Introductionmentioning
confidence: 78%
“…In the present work, a molecular dynamics (MD) simulation is used to investigate the evolution of microstructures of Si 50 Ge 50 nanoparticles during solidification. The internal microstructure of nanoparticles is examined by the pair distribution function (PDF), the coordination number (CN), and the largest standard cluster (LaSC). It is found that Si 50 Ge 50 nanodroplets with some metallicity are cooled into a crystal without element segregation through four stages, and the saturation of the covalent bond is satisfied before the directionality in the crystallization process. Interestingly, there exists a CNC state, where the average size of the crystalline structure is independent of temperature but depends on the cooling rate; and the heritability of basic crystalline atoms is not over 50% until the end of the CNC state.…”
Section: Introductionmentioning
confidence: 78%
“…Fig. 1 Comparison of g(r) for the system at 293 K and 673 K between the simulation and experiment results [13] In this work, the local structures of the model alloy were analyzed in terms of the various short range orders identified using the largest standard cluster analysis (LSCA), which is recently developed by Tian et al [7,8]. In this method, the outcome cluster is called as the largest standard cluster (LSC).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, in this paper, the rapid solidification process of liquid Mg 70 Zn 30 alloy has performed by molecular dynamics simulation, and the formation and evolution of ICOI network connectivity have analyzed with largest standard cluster analysis (LSCA) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…通过Nose-Hoover热浴法的控制 [30] , 体系在 等温等压(NPT)系综环境中运行20 ns. 最后采用 最大标准团簇分析法(LaSCA) [31] 、双体分布函数 (PDF) [32] 和可视化等方法研究GaAs晶体诱导结 晶过程中的微观结构演变.…”
Section: 模拟条件和方法unclassified